Biosensors and Biomolecular Electronics - Zor, Erhan; Zhu, Ying.; Morales Narvaez, Eden.; Cinti, Stefano; Zavan, Barbara; Dutra, Rosa.; Adeloju, Samuel; Kukkar, Deepak; Sejdic, Ervin; Garbero, Roberto; Zavan, Barbara; e; et al. (London : BioMed Central : Imprint: BioMed Central.)
Biosensors and Biomolecular Electronics is dedicated to the dissemination of cutting-edge research and technological advancements in the field of biosensors, with a primary focus on their healthcare, diagnostic, and therapeutic applications. The journal aims to bridge the gap between laboratory innovation and clinical or commercial deployment, fostering interdisciplinary collaboration and real-world impact. The journal serves as a global platform for scientists and innovators working at the intersection of bioengineering, life sciences, healthcare, and materials science, with a strong emphasis on the translation of biosensing technologies into clinical and real-world healthcare settings, including precision medicine, infectious diseases, environmental health, and toxicology. We particularly welcome contributions that advance the development and implementation of biosensors in precision medicine, enabling tailored diagnostics, monitoring, and treatment strategies. Areas in scope include: Design and Fabrication of Biosensors: Innovations in sensor architecture, nanomaterials, microfluidics, and transduction mechanisms. Biorecognition Elements: Development and application of enzymes, antibodies, nucleic acids, aptamers, and synthetic receptors. Signal Transduction and Processing: Optical, electrochemical, piezoelectric, thermal, and magnetic transduction methods. Wearable and Implantable Biosensors: Devices for continuous health monitoring, diagnostics, and therapeutic feedback. Point-of-Care and Portable Devices: Biosensors for rapid, on-site analysis in clinical, health, and safety applications. Environmental and Industrial Monitoring: Detection of pollutants, toxins, and pathogens in air, water, and industrial processes. Data Integration and AI in Biosensing: Machine learning, data analytics, and IoT integration for smart biosensing systems. Regulatory, Ethical, and Commercialization Aspects: Standards, validation, and pathways to market for biosensor technologies. .
Keywords: Materials; Detectors; Molecular probes; Biology$1 (BTechnique.s; Biomedical engineering; Nanobiotechnology; Sensors and biosensors; Biological Sensors and Probes; Biological Techniques; Biomedical Engineering and Bioengineering; Nanobiotechnology